Effect of Workload and Job Stress on Employee Performance - Yuan Stelesia Kobis; Rolland Fanggidae; Tarsisius Timuneno (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The problems in this research are as follows : 1. How workload, job stress, and employee performance in Koperasi Kredit Obor Mas Cabang Utama Ende? 2. Does workload have a positive and significant effect on employee performance inÂ  Koperasi Kredit Obor Mas Cabang Utama Ende?3. Does job stress have a positive and significant effect on employee performance Koperasi Kredit Obor Mas Cabang Utama Ende? 4. Do workload and job stress simultaneously have a positive and significant effect on employee performance Koperasi Kredit Obor Mas Cabang Utama Ende. This study aims to determine the effect of workload and Job stress partially and simultaneously on employee performance Koperasi Kredit Obor Mas Cabang Utama Ende. This research is an associative research with a quantitative approach. Data collection techniques were carried out by distributing questionnaires, conducting observations, documentation, and interviews. The sample in this study was taken using the total sample technique where the entire population was sampled with a total of 43 respondents. The results of this study indicate that partially the workload has a positive and significant effect on employee performance, as well as job stress has a positive and significant effect on employee performance. The results of this study indicate that partially the workload has a positive and significant effect on employee performance, as well as job stress has a positive and significant effect on employee performance.